Experience of quantity and quality of DNA and RNA extraction from limited pediatric blood samples: A comparative analysis of automated and manual kit-based method - Pankaj Sharma; Minu Singh; Aditya Singh; Deepshikha Bhardwaj; Prateek Bhatia (Wolters Kluwer Medknow Publications, 2022)
Introduction: Optimal DNA and RNA quantity and purity is essential for downstream molecular biology experimentation and to avoid re-processing of sample. Despite availability of different kits and automated systems for nucleic acid isolation there is limited data on their performance evaluation, more so with pediatric blood samples, that are usually compromised in quantity. Hence, we evaluated the performance of automated QIAcube platform using pediatric blood samples in parallel with manual Qiagen extraction kits. Materials and Methods: A total of 500 samples were analyzed based on groups of PBMC and direct blood input. The isolated DNA and RNA were surveyed for quantity and quality tests by spectrophotometric and downstream analysis. Results: There was no significant difference in the DNA quantity (ng/ul) between manual and automated method based on similar sample input but quality (260/280) was significantly better with the QIAcube platform when direct blood and or PBMCs were used for extraction respectively (1.82 ± 004 Vs. 1.84.002; P-0.000008 and 1.859 ± 005 Vs. 1.843 ± 0.003; P-0.02). Moreover, the standard error mean was low for both quantity and quality in the QIAcube method suggesting uniformity. Comparison of quality assessment by spectrophotometer and qubit fluorimeter showed that QIAcube sheared DNA less (P- 0.038) as compared to manual method (P-0.013). Also, time taken to process the samples in QIAcube was 23% less than the kit-based method. Conclusion: Overall analysis of QIAcube platform suggests that it yields more better, uniform, and less-sheared quality of nucleic acid in a relatively less time as compared to manual extraction kits.